The mediating role of forgiveness in the relationship between emotion regulation difficulty and relational aggression in high school students - Esra Ceyhan; Mehmet Şahan (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
The increase in aggressive behavior during adolescence has led to both research on aggression and the identification of various types of aggression by considering aggression as a multidimensional structure. One of these is relational aggression. In this context, this study aims to examine the mediating role of forgiveness in the relationship between high school students' emotion regulation difficulties and relational aggression. The relational screening method and basic mediation model were used in the study. The study group of the research consists of 1012 students attending public high schools in the center of Eskişehir in the 2021-2022 academic year. The study used the Relational Aggression in Friendship Relationships Scale Adolescent Form, the Difficulty in Emotion Regulation Scale, and the Forgiveness Scale for Adolescents. According to the study's findings, adolescents' forgiveness is directly and negatively predicted by difficulties in emotion regulation. Relational aggression is directly and negatively predicted by forgiveness. The total effect of difficulties in emotion regulation on relational aggression was .19. When the mediator variable, forgiveness, is included in the model, the total effect decreases to .17, which is significant. The indirect effect of forgiveness on adolescents' difficulty in emotion regulation and relational aggression was found to be significant. The partial mediating role of forgiveness was found to be significant, but its effect level was low. In conclusion, all these findings indicate that high school students' difficulty in emotion regulation is a risk factor for relational aggression, while forgiveness is a protective factor.